Isolation, Identification, Molecular Characterization and Antimicrobial Resistance Profiling of ESBL Positive E. coli Isolates of Cattle in Eastern Zone of Uttar Pradesh - Yadav, Vibha; Joshi, Rajesh K.; Joshi, Namita; Kumar, Amit; Srivastva, Mrinal; Singh, Satyavrat; Chaudhary, Pankaj K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
In this present study total of 240 milk and fecal samples were collected from two districts of the plain Eastern zone of Uttar Pradesh (India). Among 240 samples, a total of 135 (56.25%) isolates were confirmed as E. coli using a species-specific uidA gene oligonucleotide primer. Eighty-six (63.70%) ESBL producing E. coli isolates were recovered out of 135 isolates using confirmatory phenotypic methods. The antimicrobial resistance pattern revealed that all isolates showed (60-100%) resistance against cefotaxime, cefpodoxime, ceftriaxone, ampicillin, ceftazidime, aztreonam, etc. and 100% sensitivity against gentamicin, amikacin, chloramphenicol, and polymyxin-B. The multi-drug resistance (MDR) pattern of ESBL organisms was assessed by using the multiple antibiotic resistance (MAR) index. Out of 86 ESBL positive isolates, 70 (81.39%) E. coli was showed multi-drug resistance in the study. MAR index of these isolates was in the range from 0.25 to 0.75. The most frequently observed MAR index was 0.30 against 28 isolates. Antibiotic resistance patterns against non-βlactam antibiotics were also observed, and 51 isolates showed resistance against both β-lactam and non-β-lactam antibiotics, while 19 isolates showed resistance against only β-lactam antibiotics of different groups.